ANALISIS POLA RITME TUMBAO PADA PERMAINAN CONGA DALAM LAGU NECESITAS TU - margana, rangga; Saryanto; Srimoko, Gandung Joko; Retnowati, Tjut Etty (Program Studi Pendidikan Musik, 2022)
The purpose of this study is to describe the results of the Analysis TumbaoRhythm PatternonConga in Necesitas Tu. The research method used is qualitative with a descriptive approach. This research was carried out from October 2020 to June 2021. The results of the study can be concluded that the most popular Basic of Latin Cuban is the tumbao pattern. The tumbao pattern is the basic pattern for playing conga in salsa music. In the song Necesitas Tu there are two types of variations of the tumbao pattern, namely: variation I and variation II. It can be concluded that the song Necesitas Tu by Blue Mambo has 9 (nine) parts, namely: intro, main theme, development section, interlude, solo, intro, main theme, development section, and coda. The section that has more than one variation of the tumbao rhythm pattern is the development section. Overall there are 4 (four) techniques used in the tumbao pattern such as heel, fingertip/toe, slap, and open tone. The implication of the results of this study is to explore conga instruments that are of interest in developing percussion skills. Music education institutions are to provide adequate facilities so that students are more active in exploring conga instruments, so that students are motivated to improve their abilities or skills in processing Latin percussion instruments as well as Indonesian ethnic percussion.